Oxygen isotopes in titanite and apatite, and their potential for crustal evolution research. (15th June 2019) - Bruand, E.; Storey, C.; Fowler, M.; Heilimo, E.; ,
Abstract: Oxygen isotope analysis of zircon, often combined with geochronology and Hf isotope analysis, has been pivotal in understanding the evolution of continental crust. In this contribution, we expand the use of underexplored accessory phases (titanite and apatite) by demonstrating that their oxygen isotope systems can be robust, and by developing geochemical indicators involving O isotopes and trace element concentrations to better constrain magma petrogenesis. These minerals have the advantage over zircon of being present in less evolved magmas and being more responsive to igneous processes and crustal metamorphism. We present new data on titanite, apatite and zircon from carefully-selected granitoids through geological time: the Phanerozoic high Ba-Sr granites (Caledonian province, Scotland), Archean sanukitoids (Karelia province, Finland) and a Neoproterozoic basalt-andesite-dacite-rhyolite suite (BADR; Guernsey, Channel Island). We demonstrate: (i) that δ 18 O values of the studied accessory minerals are not affected by crystal fractionation, (ii) a strong correlation between δ 18 O in all three accessory minerals, showing that apatite and titanite can faithfully record the magmatic δ 18 O; (iii) that these accessory minerals can also record metamorphic and/or fluid circulation events during the syn- to post-magmatic history of granitoids.